Distribution and diversity of ticks determined by environmental factors in Ningxia, China - Di Tian; Xiao-Ming Cui; Run-Ze Ye; Yu-Yu Li; Ning Wang; Wan-Ying Gao; Bai-Hui Wang; Zhe-Tao Lin; Wen-Jie Zhu; Qiu-Shi Wang; Ya-Ting Liu; Hua Wei; et al. (One Health)
Ticks are important vectors of zoonotic pathogens, and represent an increasing threat for human and animal health. Considering the complex natural environments of Ningxia Hui Autonomous Region, China, we expect the diverse tick species in this region. Here, we conduct a field survey on parasitic and host-seeking ticks. A total of 10,419 ticks were collected, which belonged to nine species of four genera. There were significant differences in terms of vegetation index, altitude, and seven climatic factors among the four tick genera —Hyalomma, Dermacentor, Haemaphysalis, and Ixodes, except between Haemaphysalis and Ixodes, where no significant differences were observed in these factors. The ecological niche modelling revealed that the suitable habitats for Hyalomma asiaticum was in the northwest Ningxia, with annual ground surface temperature as the most important factor. The suitable area for Dermacentor nuttalli was in the southwest and eastern regions of Ningxia with elevation as the highest contribution. D. silvarum was best suited to the southern Ningxia also with elevation as the most important factor. The four tick species including Haemaphysalis longicornis, Hae. qinghaiensis, Hae. japonica, and Ixodes persulcatus were best suited to the southernmost Ningxia with annual precipitation as the main factors for Hae. longicornis and elevation for the other three ticks. The results of predicted potential distribution of different tick species provide a scientific basis for the prevention and control of ticks and tick-borne diseases in the region. Furthermore, the subsequent impacts of the Greening Program to regain forests and grasslands from former agricultural lands in Ningxia on tick population dynamics deserve further investigation.